Application of Programmable Tetrahedral Framework Nucleic Acid-Based Nanomaterials in Neurological Disorders: Progress and Prospects - Chen, Xingyu; Xie, Yu; Liu, Zhiqiang; Lin, Yunfeng (Frontiers in Bioengineering and Biotechnology, 2021)
Tetrahedral framework nucleic acid (tFNA), a special DNA nanodevice, is widely applied in diverse biomedical fields. Due to its high programmability, biocompatibility, tissue permeability as well as its capacity for cell proliferation and differentiation, tFNA presents a powerful tool that could overcome potential barriers in the treatment of neurological disorders. This review evaluates recent studies on the use and progress of tFNA-based nanomaterials in neurological disorders.